Symbolism and Domain of Numbers in English and Persian Metaphorical Expressions in the Light of Al-Hasnawi's Cognitive Model - Ghafel, Banafsheh; Rasekh, Abbass Eslami (Richtmann Publishing, 2012)
Cognitive linguistics views language in terms of concepts, either universal or culture specific. Language is both embodied andsituated in a specific environment; in this connection, metaphorical expressions (hereafter MEs) such as idioms, proverbs, and slang arepervasive and interesting to study. Numbers are widely used to form such MEs as ‘a cat has nine lives’, ‘third time is charm’ and ‘to bescattered to the four winds’. The present study investigates MENs in English and Persian within Al-Hasnawi's three-scheme cognitivemodel (2007). The aims are twofold: (i) to identtify the extent of culture-specify in English and Persian metaphorical expressions ofnumbers (hereafter MENs); (ii) to see how symbolic meaning of numbers is a determining factor in the construction of metaphoricalexpressions. The findings show that, although a small number of ideas in domain of numbers are shared between Persian and English,the majority of them are culture-bound and are thus filtered by symbolism, value and belief system of their host community.